CANVAS methodology and its pedagogical use in the subject of entrepreneurship and management - Paredes Veintimilla, Rosalba Verónica; Medina Chicaiza, Ricardo Patricio; Silva Castillo, Jorge Noe (SATHIRI, 2022)
This work has assumed the objective of proposing the Canvas methodology as a pedagogical strategy in Entrepreneurship and Management. The problem of the research was: the third-year students of a unified general high school of a public institution in the city of Cumandá-Ecuador, do not use any methodology in the development of a business plan. The methodological design has a quantitative approach, uses version 21 of the SPSS tool for the reliability analysis through Cronbach’s Alpha where a value of 0.98 was obtained as a result; the applied technique was the survey, carried out in Google Forms; a population of 53 students was considered. The results obtained in the pedagogical strategy were based on four phases: Diagnosis, Planning, Application and Control, the same ones that strengthen the skill of designing a business plan. For its validation, the Iadov technique was applied, where a result of 1 was obtained, which is equivalent to clear satisfaction. Its importance lies in the fact that it allows an improvement in the teaching-learning process, since students experiment with new strategies to acquire skills and new knowledge.